Comparison of the Gait Biomechanical Constraints in Three Different Type of Neuromotor Damages - Minosse, Silvia; Favetta, Martina; Romano, Alberto; Pisano, Alessandra; Summa, Susanna; Schirinzi, Tommaso; Vasco, Gessica; Castelli, Enrico; Petrarca, Maurizio (Frontiers in Human Neuroscience, 2022)
Background and objective: Absolute angle represents the inclination of a body segment relative to a fixed reference in space. This work compares the absolute and relative angles for exploring biomechanical gait constraints. Methods: Gait patterns of different neuromotor conditions were analysed using 3D gait analysis: normal gait (healthy, H), Cerebral Palsy (CP), Charcot Marie Tooth (CMT) and Duchenne Muscular Dystrophy (DMD), representing central and peripheral nervous system and muscular disorders, respectively. Forty-two children underwent gait analysis: 10 children affected by CP , 10 children by CMT , 10 children by DMD and 12 healthy children. The kinematic and kinetic parameters were collected to describe the biomechanical pattern of participants’ lower limbs. The absolute angles of thigh, leg and foot were calculated using the trigonometric relationship of the tangent. For each absolute series, the mean, range, maximum, minimum and initial contact were calculated. Kinematic and kinetic gait data were studied, and the results were compared with the literature. Results: Statistical analysis of the absolute angles showed how, at the local level, the single segments (thigh, leg and foot) behave differently depending on the pathology. However, if the lower limb is studied globally (sum of the kinematics of the three segments: thigh, leg and foot), a biomechanical constraint emerges. Conclusions: Each segment compensates separately for the disease deficit so as to maintain a global biomechanical invariance. Using a model of inter-joint co-variation could improve the interpretation of the clinical gait pattern.